2004
DOI: 10.1097/01.pcc.0000123550.68708.20
|View full text |Cite
|
Sign up to set email alerts
|

Candidemia in a pediatric intensive care unit

Abstract: Nonalbicans Candida accounted for 70% of candidemia in a pediatric intensive care unit. High-risk surveillance blood cultures aided diagnosis in about half the patients. Severity of illness and isolation of C. tropicalis were significant predictors of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
50
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 39 publications
9
50
1
2
Order By: Relevance
“…Despite the extensive use of fluconazole, the susceptibility rate to this agent remains very high (99.4% of C. albicans and C. parapsilosis isolates), similar to that reported by other authors (3,10), and it has even increased since our last study 10 years ago (14). Furthermore, as C. glabrata and C. krusei are very infrequent in the pediatric setting (2,3,10,12,14,22,23,26), fluconazole is still a reasonable option for fungemia treatment before species identification, except in children with prior azole exposure, as is recommended by the latest guidelines published (7,11). Except intrinsically resistant species (T. asahii and R. glutinis), echinocandins show a broad antifungal activity; only two C. parapsilosis isolates and one C. tropicalis isolate were resistant to micafungin or/and anidulafungin.…”
Section: Discussionsupporting
confidence: 65%
“…Despite the extensive use of fluconazole, the susceptibility rate to this agent remains very high (99.4% of C. albicans and C. parapsilosis isolates), similar to that reported by other authors (3,10), and it has even increased since our last study 10 years ago (14). Furthermore, as C. glabrata and C. krusei are very infrequent in the pediatric setting (2,3,10,12,14,22,23,26), fluconazole is still a reasonable option for fungemia treatment before species identification, except in children with prior azole exposure, as is recommended by the latest guidelines published (7,11). Except intrinsically resistant species (T. asahii and R. glutinis), echinocandins show a broad antifungal activity; only two C. parapsilosis isolates and one C. tropicalis isolate were resistant to micafungin or/and anidulafungin.…”
Section: Discussionsupporting
confidence: 65%
“…Hypokalemia was most frequently found in females however in the present study, hypokalemia is not significantly associated with females rather it is distributed equally in males as well as females. 2 Hypokalemia is also a common problem in pediatric intensive care unit patients; this has been reported by Singhi S et al 4 In the present age group between 40 to 60 were most affected and less than 20 years of age group individuals are the least affected.…”
Section: Discussionsupporting
confidence: 52%
“…Other Indian studies also have documented shift to these species, C. tropicalis being the most commonly isolated. 3,4 Emergence of Candida spp. other than C. albicans is due to selection of less susceptible species by the pressure of antifungal agent such as ß uconazole apart from associated risk factors and underlying disorders.…”
Section: Discussionmentioning
confidence: 99%
“…other than C. albicans. 3,4 Candida spp., which have been implicated are C. tropicalis, C. glabrata and C. parapsilosis. Previous studies have suggested that possible risk factors for candidaemia are antibiotic therapy, chemotherapy, presence of intravascular catheters, malignancy, surgery, parenteral nutrition, intensive care unit stay and prior fungal colonization.…”
Section: Abstract: Candidaemia Candida Tropicalis Candida Sppmentioning
confidence: 99%